The Combination of Softball Handling Exercise and ROM Increases Upper Extremity Muscle Strength in Non-Haemoragic Stroke Patients - Ade Lestiani Limaretha; Mugi Hartoyo; Syamsul Arif (JENDELA NURSING JOURNAL, 2020)
Background: Stroke is a brain tissues damage caused by blood supply disruption to the brain. Effects that often occurs in stroke patients is weakness in one side of the body, such as the upper extremity. Exercises to stimulate muscle hands strength can be a combination softball handling exercise and ROM. Purpose: This research aims to determine the effect of a combination softball handling exercise and ROM on muscle strength in non haemoragic stroke patients at Roemani Muhammadiyah Semarang Hospital.Methods: Type of research is Quasi Experiment with a non-rondomised control group pre-post test design. There were 32 respondents including in this research using purposive sampling to select the sample. The research data were analyzed using the Wilcoxon Test to determine the effect on the intervention group and control group, then tested using the Mann Whitney test to determine the effectiveness difference between a intervention group and control group.Results: the Wilcoxon Test showed that there was an effect of a combination softball handlingand ROM on muscle strength in non haemoragic stroke patients (p value 0.000), and there was an effect on the control group without intervention (p value 0.003). While the Mann Whitney test showed that the combination group was more effective in increasing the muscle strength p value = 0.001 (0.05).Conclusion: There is the effect of a combination of softball handling exercise and ROM on the strength of the extremity muscles over non haemoragic stroke pastients.